Privacy and Security Implementation in Existing Cloud Based Electronic Health Records - A DetailedReview - S. Prathima,Dr.C. Priya, (International Journal of Advanced Science and Technology, 2020)
Over the recent years, cloud computing has emerged as a powerful means for providing automatedhealthcare facilities. Cloud helps in massive sharing of information between doctors and hospitals usingElectronic Health Records. This major transformation has changed the way doctors and hospitals deliverquality and effective service to their patients. Using Cloud storage inhealthcare services has revolutionized health industry, making it more efficient. Apart from the primary driving factors of cloud like flexibility in cost of maintenance, infrastructure and development, on-demand scalability of storage centers andpay on use schemes are proven to be most effective. More and more digitalization of data causes breechof security and privacy.Because healthcare information is a highly sensitive data which cannot be compromised,the future of healthcare relies in providing secure and trustworthy sharing of data by safeguarding privacy and trust. This paper gives an extensive review of the existing security mechanisms forCloud based healthcare systems.